Boosting energy-storage performance in lead-free ceramics via polyphase engineering in the superparaelectric state. (15th April 2023) - Cao, Wenjun; Chen, Pengfei; Lin, Renju; Li, Feng; Ge, Binghui; Song, Dongsheng; Cheng, Zhenxiang; Wang, Chunchang
Abstract: Dielectric energy storage devices are important components of high-power and pulsed electronic systems. High recoverable energy density ( W rec ) and high efficiency ( ƞ ) are critical parameters for such applications. In this work we propose a strategy of polyphase engineering in the superparaelectric (SPE) state to achieve high-performance energy storage. Through careful engineering of the proportions of rhombic ( R ) phase and tetragonal ( T ) phase by a linear dielectric additive, CaTi0.8 Hf0.2 O3 (CTH), in 0.94Na0.5 Bi0.5 TiO3 -0.06BaTiO3 -based ceramics, the SPE state can be shifted to ambient temperature when R/T  ≤ 0.16. Thanks to the features of isolated polar nano-domains (PNRs) and the fine P-E hysteresis loop of the SPE state, an ultrahigh W rec of 8.91 J/cm 3 and high ƞ of 78.4% are achieved in our 0.75(0.94Na0.5 Bi0.5 TiO3 -0.06BaTiO3 )-0.25CaTi0.8 Hf0.2 O3 sample. The sample was also characterized by excellent temperature and frequency stability, achieving ultra-high power density (178 MW/cm 3 ) and ultra-fast transient discharge time (40 ns). Our work proves that polyphase engineering in the SPE state is a powerful approach to the design of dielectric energy storage materials with high performance.